Composite solid electrolyte, preparation method thereof, and all-solid-state battery comprising composite solid electrolyte

By forming a composite solid electrolyte with a polymer coating on the sulfide-based solid electrolyte particles, the problem of high reactivity of the sulfide-based solid electrolyte to moisture is solved, the atmospheric stability and chemical resistance are significantly improved, the generation of harmful gases is reduced, and the safety and performance of the battery are ensured.

CN119654730APending Publication Date: 2025-03-18LG CHEM LTD

Patent Information

Application Number
CN202380060095.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-30
Filing Date
2023-08-24
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The sulfide-based solid electrolyte is highly reactive to moisture, which leads to reaction with moisture in the air and moisture under low humidity conditions, producing harmful gas hydrogen sulfide, affecting safety and performance.

Method used

Using a composite solid electrolyte containing a polymer coating on sulfide-based solid electrolyte particles, the polymer coating contains repeating units represented by chemical formula I, and the coating is formed by heat treatment to improve atmospheric stability and chemical resistance.

Benefits of technology

It significantly improves the atmospheric stability and chemical resistance of the composite solid electrolyte, reduces the amount of hydrogen sulfide produced, ensures the safety of the process and improves the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The present invention addresses the problem of improving the atmospheric stability of a conventional sulfide-based solid electrolyte, and relates to a composite solid electrolyte, a method for manufacturing the same, and an all-solid-state battery comprising the same. The composite solid electrolyte includes: sulfide-based solid electrolyte particles; and a polymer coating layer formed on the sulfide-based solid electrolyte particles, wherein a polymer in the polymer coating layer contains a repeating unit represented by chemical formula (I) described herein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0109284, filed on August 30, 2022, the disclosure of which is incorporated herein by reference. Technical Field

[0003] The present invention relates to a sulfide-based composite solid electrolyte with improved atmospheric stability and chemical resistance, a preparation method thereof, and an all-solid-state battery comprising the sulfide-based composite solid electrolyte. Background Art

[0004] An all-solid-state battery is a battery that replaces the liquid electrolyte filled between the positive and negative electrodes of a conventional lithium secondary battery with a solid. It has attracted much attention as a next-generation battery because it has a higher energy density than conventional batteries and is safe because there is no risk of explosion. The solid electrolyte used in an all-solid-state battery is a solid-state material that can conduct lithium ions in the battery, wherein it has a high ion conductivity comparable to the ion conductivity of the electrolyte currently used in lithium secondary batteries. The core materials that constitute the solid electrolyte include polymers, sulfides or oxides, but among them, sulfide-based solid electrolytes with high flexibility and ion conductivity are evaluated as suitable for preparing high-capacity large batteries.

[0005] However, since the sulfide-based solid electrolyte is highly reactive to moisture, the problem is that it reacts not only with moisture in the air but also with moisture under low humidity conditions to produce harmful gas hydrogen sulfide (H2S). Therefore, the toxic hydrogen sulfide may not only adversely affect the safety of workers, but also deteriorate the performance of the sulfide-based solid electrolyte itself.

[0006] Therefore, there is a need to develop a sulfide-based solid electrolyte having excellent atmospheric stability and chemical resistance. Summary of the invention

[0007] Technical issues

[0008] An object of the present invention is to provide a composite solid electrolyte having improved atmospheric stability and chemical resistance.

[0009] However, the objects of the present invention are not limited to the above objects, and other objects not described herein will be clearly understood by those skilled in the art from the following description.

[0010] Technical Solution

[0011] In order to solve the above-mentioned task, the present invention provides a composite solid electrolyte, a method for preparing the composite solid electrolyte and an all-solid-state battery.

[0012] (1) The present invention provides a composite solid electrolyte comprising sulfide-based solid electrolyte particles; and a polymer coating formed on the sulfide-based solid electrolyte particles, wherein the polymer of the polymer coating contains a repeating unit represented by Chemical Formula I,

[0013] [Chemical Formula I]

[0014]

[0015] In Chemical Formula I,

[0016] X is fluorine (F) or chlorine (Cl).

[0017] (2) The present invention provides the composite solid electrolyte described in (1) above, wherein the polymer of the polymer coating layer contains a repeating unit represented by Chemical Formula 1,

[0018] [Chemical formula 1]

[0019] .

[0020] (3) The present invention provides the composite solid electrolyte described in (1) or (2) above, wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure.

[0021] (4) The present invention provides the composite solid electrolyte described in any one of (1) to (3) above, wherein the weight average molecular weight (Mw) of the polymer of the polymer coating layer is 1,000 g / mol to 1,000,000 g / mol.

[0022] (5) The present invention provides the composite solid electrolyte described in any one of (1) to (4) above, wherein the content of the polymer coating layer is 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the sulfide-based solid electrolyte particles.

[0023] (6) The present invention provides the composite solid electrolyte described in any one of (1) to (5) above, wherein the initial ion conductivity of the composite solid electrolyte is in the range of 0.001 mS / cm to 20 mS / cm.

[0024] (7) The present invention provides a composite solid electrolyte as described in any one of (1) to (6) above, wherein when the composite solid electrolyte is exposed to an air atmosphere at a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the amount of hydrogen sulfide (H2S) generated in the first hour is 10 cm3 / g of the composite solid electrolyte. 3 the following.

[0025] (8) The present invention provides a method for preparing a composite solid electrolyte as described in any one of (1) to (7) above, comprising the steps of: (A) mixing a polymer containing a repeating unit represented by Chemical Formula I with a sulfide-based solid electrolyte to prepare a mixture; and (B) heat-treating the mixture at a temperature higher than the melting point of the polymer to form a polymer coating on particles of the sulfide-based solid electrolyte.

[0026] [Chemical Formula I]

[0027]

[0028] In Chemical Formula I,

[0029] X is F or Cl.

[0030] (9) The present invention provides the method according to (8) above, wherein the polymer contains a repeating unit represented by Chemical Formula 1,

[0031] [Chemical formula 1]

[0032] .

[0033] (10) The present invention provides the method described in (8) or (9) above, wherein in the step (A), the polymer is mixed in an amount of 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the sulfide-based solid electrolyte.

[0034] (11) The present invention provides the method according to any one of (8) to (10) above, wherein the mixing is dry mixing.

[0035] (12) The present invention provides the method according to any one of (8) to (11) above, wherein the heat treatment temperature is in the range of 180°C to 250°C.

[0036] (13) The present invention provides an all-solid-state battery comprising the composite solid electrolyte described in any one of (1) to (7) above.

[0037] Beneficial Effects

[0038] Since the composite solid electrolyte according to the present invention has a polymer coating having excellent atmospheric stability and chemical resistance formed on sulfide-based solid electrolyte particles, the composite solid electrolyte itself not only has excellent atmospheric stability but also can improve chemical resistance in a wet process when preparing a battery. DETAILED DESCRIPTION

[0039] Hereinafter, the present invention will be described in more detail to make the understanding of the present invention clearer.

[0040] It should be understood that the words or terms used in this specification and claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that the words or terms should be interpreted as having meanings consistent with their meanings in the context of the prior art and technical concepts of the present invention, based on the principle that the inventor can appropriately define the meanings of the words or terms to best explain the present invention.

[0041] The terms used herein are for the purpose of describing specific example embodiments only and are not intended to limit the present invention.In the present specification, unless otherwise specified, terms in the singular form may include plural forms.

[0042] It should also be understood that when used in this specification, the terms "includes", "comprising" or "having" specify the existence of the stated features, numbers, steps, elements or their combinations, but do not exclude the existence or addition of one or more other features, numbers, steps, elements or their combinations.

[0043] In the present specification, "*" is a linking site between repeating units, and when it is a terminal, it is fluorine (F), chlorine (Cl) or hydrogen (H).

[0044] Composite solid electrolyte

[0045] The composite solid electrolyte according to the present invention comprises sulfide-based solid electrolyte particles; and a polymer coating formed on the sulfide-based solid electrolyte particles, wherein the polymer of the polymer coating contains a repeating unit represented by the following chemical formula I,

[0046] [Chemical Formula I]

[0047]

[0048] In Chemical Formula I,

[0049] X is F or Cl.

[0050] According to the present invention, the polymer of the polymer coating may contain a repeating unit represented by the following Chemical Formula 1:

[0051] [Chemical formula 1]

[0052]

[0053] The inventors have discovered that, for the composite solid electrolyte according to the present invention, since a polymer coating having excellent atmospheric stability (excellent moisture and oxygen barrier properties) is formed on the sulfide-based solid electrolyte particles, the composite solid electrolyte itself not only has excellent atmospheric stability, but also can improve chemical resistance in dry and wet processes when preparing batteries, thereby completing the present invention.

[0054] In the composite solid electrolyte according to the present invention, since the polymer coating layer contains a polymer containing a repeating unit represented by Chemical Formula I, specifically a polymer containing a repeating unit represented by Chemical Formula 1, decomposition and degradation of the sulfide-based solid electrolyte particles when exposed to moisture or oxygen can be suppressed. As a result, the generation of toxic gas hydrogen sulfide can be suppressed. In addition, the reduction of the ion conductivity of the composite solid electrolyte can be prevented.

[0055] In the composite solid electrolyte according to the present invention, since the polymer coating contains a polymer containing a repeating unit represented by Chemical Formula I, specifically a polymer containing a repeating unit represented by Chemical Formula 1, having a lower moisture permeability than a polymer such as PTFE, PDMS or EVA, the sulfide-based solid electrolyte particles can be better prevented from contacting with moisture.

[0056] According to the present invention, in terms of further improving moisture stability, specifically, the polymer may consist of only the repeating unit represented by Chemical Formula 1. That is, the polymer may be polychlorotrifluoroethylene (PCTFE).

[0057] According to the present invention, the sulfide-based solid electrolyte may have an argyrodite-type crystal structure in terms of high ion conductivity and low reactivity with a lithium negative electrode. The sulfide-based solid electrolyte may be a sulfide-based solid electrolyte containing lithium (Li), phosphorus (P) and sulfur (S).

[0058] For example, the sulfide-based solid electrolyte may have a composition represented by the following Chemical Formula 2. In this case, the composite solid electrolyte according to the present invention may have high ion conductivity and may have low reactivity with a lithium negative electrode, and may suppress decomposition and degradation of the sulfide-based solid electrolyte particles when exposed to moisture or oxygen.

[0059] [Chemical formula 2]

[0060] Li a (P 1-b M b )S cX d

[0061] In Chemical Formula 2,

[0062] M is at least one selected from silicon (Si), tin (Sn), niobium (Nb), nickel (Ni), germanium (Ge), gallium (Ga), and aluminum (Al),

[0063] X is at least one selected from fluorine (F), chlorine (Cl), bromine (Br), and iodine (I), and

[0064] 5.0 < a < 7.5, 0 ≤ b ≤ 0.7, 3.5 ≤ c ≤ 7, and 0.8 ≤ d ≤ 1.7.

[0065] M is a doping element doped into the solid electrolyte having a thiogalena-type crystal structure, where M can be at least one selected from Sn, Nb, Ni, Ge, Ga, and Al, specifically at least one selected from Sn, Nb, Ge, and Al.

[0066] According to the present invention, the weight-average molecular weight (Mw) of the polymer of the polymer coating can be from 1,000 g / mol to 1,000,000 g / mol. Specifically, the weight-average molecular weight (Mw) of the polymer of the polymer coating can be 1,000 g / mol or more, 200,000 g / mol or less, 500,000 g / mol or less, or 1,000,000 g / mol or less. When the weight-average molecular weight (Mw) of the polymer is within the above range, since a uniform and thin polymer coating can be formed, the water barrier effect can be further improved while minimizing the reduction in ionic conductivity.

[0067] According to the present invention, the content of the polymer coating can be from 0.1 parts by weight to 10 parts by weight with respect to 100 parts by weight of the sulfide-based solid electrolyte particles. Specifically, the content of the polymer coating can be 0.1 parts by weight or more, 0.5 parts by weight or more, 5 parts by weight or less, 7 parts by weight or less, and 10 parts by weight or less with respect to 100 parts by weight of the sulfide-based solid electrolyte particles. In this case, the water barrier effect can be improved, and the reduction in ionic conductivity can be minimized.

[0068] According to the present invention, the initial ionic conductivity of the composite solid electrolyte can be from 0.001 mS / cm to 20 mS / cm, specifically 0.001 mS / cm or more, 0.01 mS / cm or more, 5 mS / cm or less, 10 mS / cm or less, or 20 mS / cm or less. The higher the ionic conductivity of the electrolyte, the better, but when the initial ionic conductivity satisfies the above range, the effect of improving water stability may be excellent.

[0069] The initial ion conductivity is a value calculated from the resistance value measured in a drying room at a temperature of 22° C. and a relative humidity of 0.7% immediately after the preparation of the composite solid electrolyte. Specifically, the initial ion conductivity is a value calculated by the following method.

[0070] i) immediately after the preparation of the composite solid electrolyte, 150 mg of the composite solid electrolyte powder was taken and placed in a SUS mold with a diameter of 13 mm;

[0071] ii) in a state where the SUS mold is mounted on a press together with PEEK for insulation, a potentiostat is connected to the mold, and then the electrolyte structure is sufficiently densified by pressing at a pressure of 370 MPa, and then AC impedance measurement is performed at a measurement frequency of 1 Hz to 7 MHz while the pressure is slowly reduced and maintained at 100 MPa;

[0072] iii) Calculate the ionic conductivity from the measured resistance values ​​using the Nyquist plot.

[0073] According to the present invention, when the composite solid electrolyte is exposed to an air atmosphere having a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the amount of hydrogen sulfide (H2S) generated in the first hour is 10 cm3 / 1 g of the composite solid electrolyte. 3 the following.

[0074] That is, since the composite solid electrolyte according to the present invention has excellent moisture stability, the generation amount of toxic gas hydrogen sulfide is small and the generation rate is slow, so process safety can be ensured.

[0075] Method for preparing composite solid electrolyte

[0076] The composite solid electrolyte according to the present invention can be prepared by coating sulfide-based solid electrolyte particles with a polymer composition including a polymer containing a repeating unit represented by the following Chemical Formula I.

[0077] [Chemical Formula I]

[0078]

[0079] In Chemical Formula I,

[0080] X is F or Cl.

[0081] According to the present invention, the polymer may contain a repeating unit represented by the following Chemical Formula 1.

[0082] [Chemical formula 1]

[0083]

[0084] Specifically, the method for preparing a composite solid electrolyte according to the present invention comprises the following steps: (A) mixing a polymer containing a repeating unit represented by Chemical Formula I with a sulfide-based solid electrolyte to prepare a mixture; and (B) heat-treating the mixture at a temperature higher than the melting point of the polymer to form a polymer coating on particles of the sulfide-based solid electrolyte.

[0085] Step (A)

[0086] Step (A) is a step of preparing a mixture by mixing a polymer containing a repeating unit represented by Chemical Formula I (specifically, a polymer containing a repeating unit represented by Chemical Formula 1) with a sulfide-based solid electrolyte.

[0087] The polymer containing the repeating unit represented by Chemical Formula I, the polymer containing the repeating unit represented by Chemical Formula 1, and the sulfide-based solid electrolyte are the same as those described in the composite solid electrolyte according to the present invention.

[0088] The sulfide-based solid electrolyte can be synthesized, for example, by mechanical grinding and solid phase synthesis. Specifically, the sulfide-based solid electrolyte can be prepared by the following steps: weighing three precursors of Li2S, P2S5 and LiCl according to stoichiometry, then mixing them by ball milling, crystallizing the thus obtained mixed precursor by heat treatment, and then grinding again by ball milling. In this case, the mixing, heat treatment and grinding processes can be carried out in an inert gas atmosphere.

[0089] According to the present invention, in step (A), the polymer may be mixed in an amount of 0.1 to 10 parts by weight relative to 100 parts by weight of the sulfide-based solid electrolyte. Specifically, the polymer may be mixed in an amount of 0.1 parts by weight or more, 1 part by weight or more, 2 parts by weight or more, 6 parts by weight or less, 7 parts by weight or less, or 10 parts by weight or less relative to 100 parts by weight of the sulfide-based solid electrolyte. In this case, since a uniform polymer coating is formed, a composite solid electrolyte having excellent moisture barrier effect and appropriate ion conductivity can be prepared.

[0090] According to the present invention, the mixing may be dry mixing. Specifically, the mixing may be ball milling of the polymer and the sulfide-based solid electrolyte particles. The dry mixing may be performed using a planetary ball mill into which zirconia balls are introduced, and may be performed while rotating at a speed of 100 to 200 rpm for uniform mixing.

[0091] Step (B)

[0092] Step (B) is a step of heat-treating the mixture at a temperature higher than the melting point of the polymer to form a polymer coating on the particles of the sulfide-based solid electrolyte. In other words, it is a step of melting the polymer to form a polymer coating on the particles of the sulfide-based solid electrolyte.

[0093] According to the present invention, the heat treatment temperature may be in the range of 180° C. to 250° C., particularly 180° C. to 230° C., and more particularly 180° C. to 220° C. In this case, since the aggregation of the electrolyte particles can be minimized while the polymer is fully melted, there is an advantage in forming a uniform composite solid electrolyte.

[0094] The heat treatment may be performed in an inert atmosphere to prevent side reactions.

[0095] The heat treatment may be performed for 1 hour to 8 hours, specifically 1 hour or more, 2 hours or more, 4 hours or less, 5 hours or less, or 8 hours or less, so as to minimize aggregation of the electrolyte particles while the polymer is sufficiently melted.

[0096] All-solid-state battery

[0097] The present invention provides an all-solid battery comprising the composite solid electrolyte.

[0098] Specifically, the all-solid battery includes: a positive electrode including a positive electrode active material, a negative electrode including a negative electrode active material, and a solid electrolyte layer disposed between the positive electrode and the negative electrode and including the composite solid electrolyte according to the present invention.

[0099] Since the all-solid battery according to the present invention has excellent moisture stability, the initial efficiency, life characteristics, and output characteristics of the battery may be excellent.

[0100] In this case, the all-solid battery of the present invention can be prepared according to a typical method known in the art. For example, the all-solid battery of the present invention can be prepared by stacking and pressing the solid electrolyte layer between the positive electrode and the negative electrode.

[0101] (1) Positive electrode

[0102] The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent.

[0103] There is no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, fine concavities and convexities can be formed on its surface to improve the bonding strength with the positive electrode active material, and the positive electrode current collector can be used in various shapes such as films, sheets, foils, meshes, porous bodies, foams, non-woven fabric bodies, etc.

[0104] The positive electrode active material is a compound capable of reversibly intercalating and deintercalating lithium, and specifically, the positive electrode active material may include a lithium metal oxide, and the lithium metal oxide includes lithium and at least one metal such as cobalt, manganese, nickel, or aluminum. More specifically, the lithium metal oxide may include: lithium manganese-based oxides (such as LiMnO2, LiMn2O4, etc.), lithium cobalt-based oxides (such as LiCoO2, etc.), lithium nickel-based oxides (such as LiNiO2, etc.), lithium nickel manganese-based oxides (such as LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), lithium nickel cobalt-based oxides (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), lithium manganese cobalt-based oxides (such as LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), lithium nickel manganese cobalt-based oxides (such as Li(Ni p Co q Mn r1 )O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2), etc.), or lithium nickel cobalt transition metal (M) oxides (such as Li(Ni p2 Co q2 Mn r3 M S2)O2, where M is selected from aluminum (Al), iron (Fe), vanadium (V), chromium (Cr), titanium (Ti), tantalum (Ta), magnesium (Mg), and molybdenum (Mo), and p2, q2, r3, and S2 are the atomic fractions of the respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, and p2 + q2 + r3 + S2 = 1), etc., and may include any one of them or a mixture of two or more thereof.

[0105] Among these materials, in terms of improving the capacity characteristics and stability of the battery, the lithium metal oxide may be LiCoO2, LiMnO2, LiNiO2, lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 )O2, Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium nickel cobalt aluminum oxide (e.g., LiNi 0.8 Co 0.15 Al 0.05 O2, etc.), and, considering the significant improvement effect caused by controlling the type and content ratio of the components constituting the lithium composite metal oxide, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, and Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and any one of them or a mixture of two or more thereof may be used.

[0106] The content of the positive electrode active material may be 60% by weight to 99% by weight, particularly 70% by weight to 99% by weight, more particularly 80% by weight to 98% by weight, based on the total weight of the solids excluding the solvent in the positive electrode paste.

[0107] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0108] The binder may be generally contained in an amount of 1 to 20 wt %, particularly 1 to 15 wt %, and more particularly 1 to 10 wt %, relative to the total weight of solids excluding the solvent in the positive electrode slurry.

[0109] The conductive material is a component for further improving the conductivity of the positive electrode active material.

[0110] There is no particular limitation on the conductive material as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, conductive materials such as graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0111] The conductive material may be generally contained in an amount of 1 to 20 wt %, particularly 1 to 15 wt %, and more particularly 1 to 10 wt %, relative to the total weight of solid matter excluding the solvent in the positive electrode slurry.

[0112] The solvent may include an organic solvent such as N-methyl-2-pyrrolidone (NMP) and may be used in an amount such that a desired viscosity is obtained when the positive electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solids containing the positive electrode active material and the optional binder and the conductive material is in the range of 50% to 95% by weight, particularly 70% to 95% by weight, and more particularly 70% to 90% by weight.

[0113] (2) Negative electrode

[0114] The negative electrode may be prepared, for example, by coating a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode collector, or a graphite electrode formed of carbon (C) or a metal itself may be used as the negative electrode.

[0115] For example, in the case where the negative electrode is prepared by coating the negative electrode slurry on the negative electrode collector, the negative electrode collector generally has a thickness of 3 μm to 500 μm. There is no particular limitation on the negative electrode collector as long as it has high conductivity and does not cause adverse chemical changes in the battery, for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, or copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, similar to the positive electrode collector, the negative electrode collector may have a fine surface roughness to improve the bonding strength with the negative electrode active material, and the negative electrode collector may be used in various shapes such as a film, a sheet, a foil, a mesh, a porous body, a foam, a non-woven fabric body, etc.

[0116] The negative electrode active material may include at least one negative electrode active material selected from the group consisting of natural graphite, artificial graphite, carbonaceous materials, lithium-containing titanium composite oxide (LTO), silicon (Si), SiO x , such as Sn, lithium (Li), zinc (Zn), magnesium (Mg), cadmium (Cd), cerium (Ce), Ni or Fe; an alloy composed of the metal (Me); an oxide (MeO x ); and a composite material of the metal (Me) and carbon. Specifically, as the negative electrode active material, a silicon-based negative electrode active material containing silicon (Si), silicon oxide (SiOx) or a silicon alloy can be used. In this case, since a thin and stable SEI layer containing siloxane bonds is formed, the high temperature stability and life characteristics of the battery can be further improved.

[0117] The negative electrode active material may be contained in an amount of 60 to 99 wt %, particularly 70 to 99 wt %, and more particularly 80 to 98 wt % relative to the total weight of solids excluding the solvent in the negative electrode slurry.

[0118] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0119] The binder may be generally contained in an amount of 1 to 20 wt %, particularly 1 to 15 wt %, and more particularly 1 to 10 wt %, relative to the total weight of solids excluding the solvent in the negative electrode slurry.

[0120] The conductive material is a component for further improving the conductivity of the negative electrode active material. There is no particular limitation on the conductive material as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, conductive materials such as graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives.

[0121] The conductive material may be contained in an amount of 1 to 20 wt %, particularly 1 to 15 wt %, and more particularly 1 to 10 wt %, relative to the total weight of solid matter excluding the solvent in the negative electrode slurry.

[0122] The solvent may include water or an organic solvent, such as NMP (N-methyl-2-pyrrolidone), and may be used in an amount such that a desired viscosity is obtained when the negative electrode active material and the optional binder and the conductive material are included. For example, the content of the solvent may be such that the concentration of the solids containing the negative electrode active material and the optional binder and the conductive material is in the range of 50% to 95% by weight, specifically 70% to 90% by weight.

[0123] In the case where a metal itself is used as the negative electrode, the negative electrode may be a metal film itself, or may be prepared by physically combining, rolling or depositing the metal on the negative electrode current collector. As the deposition method, an electrodeposition method or a chemical vapor deposition method for the metal may be used.

[0124] For example, the metal film itself or the metal to be bonded / rolled / deposited on the negative electrode current collector may contain one type of metal selected from lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In) or an alloy of two types of metals.

[0125] (3) Solid electrolyte layer

[0126] In addition to containing the solid electrolyte according to the present invention, the solid electrolyte layer may further contain a binder.

[0127] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber, fluororubber or various copolymers thereof.

[0128] The content of the binder may generally be 1 wt % to 20 wt %, specifically 1 wt % to 15 wt %, more specifically 1 wt % to 10 wt %, relative to the total weight of the solid electrolyte layer.

[0129] The present invention provides a battery module including an all-solid battery as a unit cell, and can provide a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate capability and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the following: electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.

[0130] Mode for Carrying Out the Invention

[0131] Below, preferred embodiments will be provided to better understand the present invention. It will be apparent to those skilled in the art that these embodiments are only provided to illustrate the present invention, and various modifications and changes are possible within the scope and technical spirit of the present invention. Such modifications and changes fall within the scope of the claims included herein.

[0132] Preparation Example

[0133] The three precursors of Li2S, P2S5 and LiCl were dry mixed (ball milled) at a molar ratio of 5:1:2. During dry mixing, a planetary ball mill introduced with zirconium oxide balls was used and rotated at a speed of 300 rpm to 700 rpm for uniform mixing. Thereafter, the mixed precursor thus obtained was crystallized by heat treatment at 600°C for 12 hours and then ground again by ball milling to prepare Li6PS5Cl powder having a argyrodite-type crystal structure. All of the above processes were carried out in an inert argon (Ar) atmosphere.

[0134] Examples and Comparative Examples

[0135] Example 1

[0136] A mixture was prepared by dry mixing (ball milling) PCTFE (Mw: 20,000 g / mol) as a polymer and Li6PS5Cl powder having an argyrodite-type crystal structure prepared in the preparation example at a weight ratio of 5:95. During the dry mixing, a planetary ball mill introduced with zirconia balls was used and rotated at a speed of 100 rpm to 200 rpm for uniform mixing. The mixture was heat treated at a temperature range of 180°C to 250°C for 2 hours to form a polymer coating on the Li6PS5Cl particles having an argyrodite-type crystal structure. All of the above processes were performed in an inert Ar atmosphere.

[0137] As a result, a composite solid electrolyte was obtained in which a polymer coating layer containing PCTFE was formed on Li6PS5Cl particles having an argyrodite-type crystal structure.

[0138] Example 2

[0139] A composite solid electrolyte in which a polymer coating containing PCTFE was formed on Li6PS5Cl particles having an argyrodite-type crystal structure was prepared in the same manner as in Example 1, except that PCTFE (Mw: 150,000 g / mol) was used instead of PCTFE (Mw: 20,000 g / mol) as the polymer.

[0140] Comparative Example 1

[0141] The Li6PS5Cl powder having an argyrodite-type crystal structure prepared in the Preparation Example was used as the solid electrolyte of Comparative Example 1.

[0142] Comparative Example 2

[0143] A composite solid electrolyte in which a polymer coating containing PTFE was formed on Li6PS5Cl particles having an argyrodite-type crystal structure was prepared in the same manner as in Example 1, except that PTFE (polytetrafluoroethylene) (Sigma-Aldrich) was used as the polymer and heat treatment was performed at 330°C for 2 hours.

[0144] Comparative Example 3

[0145] A composite solid electrolyte in which a polymer coating layer containing PDMS was formed on Li6PS5Cl particles having an argyrodite-type crystal structure was prepared in the same manner as in Example 1, except that PDMS (JNC Corporation, Silaplane FM-0725) was used as the polymer.

[0146] Comparative Example 4

[0147] A composite solid electrolyte in which a polymer coating containing EVA was formed on Li6PS5Cl particles having an argyrodite-type crystal structure was prepared in the same manner as in Example 1, except that EVA (ethylene-vinyl acetate copolymer) (Sigma-Aldrich) was used as the polymer.

[0148]

[0149] Experimental Example 1: Evaluation of initial ion conductivity

[0150] After the preparation of the composite solid electrolyte powders of Examples 1 and 2, 150 mg of each composite solid electrolyte powder was immediately taken and placed in a SUS mold with a diameter of 13 mm. In a state where the SUS mold was mounted on a press together with PEEK for insulation, a constant potentiostat was connected to the mold. After the electrolyte structure was fully densified by pressing at a pressure of 370 MPa, the AC impedance measurement was performed at a measurement frequency of 1 Hz to 7 MHz while slowly reducing the pressure and maintaining it at 100 MPa. The ionic conductivity was calculated from the measured resistance values ​​by the Nyquist plot and is shown in Table 2 below. All measurements were carried out in a drying chamber at a temperature of 22 ° C and a relative humidity of 0.7%.

[0151]

[0152] Referring to Table 2, it can be confirmed that the composite solid electrolytes according to Examples 1 and 2 of the present invention have initial ion conductivity at a level capable of driving a battery.

[0153] Experimental Example 2: Evaluation of Hydrogen Sulfide Gas Generation

[0154] 5 mg of each of the composite solid electrolytes of Examples 1 and 2, the solid electrolyte of Comparative Example 1, and the composite solid electrolyte powders of Comparative Examples 2 to 4 were placed in a glove box equipped with a hydrogen sulfide sensor (in a dry air atmosphere controlled at a temperature of 25°C and a relative humidity of 0.59%) for more than 1 hour. The amount of hydrogen sulfide generated per 1 g of the composite solid electrolyte was calculated from the amount of hydrogen sulfide generated within 1 hour from the moment of placement, and is shown in Table 3 below.

[0155]

[0156] Referring to Table 3, for the composite solid electrolytes according to Examples 1 and 2 of the present invention, it can be confirmed that the amount of toxic gas hydrogen sulfide generated is less than that of the solid electrolyte of the comparative example, so it can be confirmed that the composite solid electrolytes according to Examples 1 and 2 of the present invention have better moisture stability.

[0157] Therefore, for the composite solid electrolyte according to the present invention, since the polymer coating layer contains a polymer containing a repeating unit represented by the chemical formula I described herein, it can be understood that the decomposition and degradation of the sulfide-based solid electrolyte particles during exposure to moisture or oxygen can be suppressed. As a result, it can be understood that the composite solid electrolyte according to the present invention itself not only has excellent atmospheric stability, but also can ensure the safety of dry and wet processes when preparing a battery.

Claims

1. A composite solid electrolyte comprising: Sulfide-based solid electrolyte particles; and forming a polymer coating on the sulfide-based solid electrolyte particles, The polymer of the polymer coating comprises a repeating unit represented by Chemical Formula I: [Chemical Formula I] in, In Chemical Formula I, X is fluorine (F) or chlorine (Cl).

2. The composite solid electrolyte according to claim 1, wherein the polymer of the polymer coating comprises a repeating unit represented by Chemical Formula 1: [Chemical formula 1] 。 3 . The composite solid electrolyte according to claim 1 , wherein the sulfide-based solid electrolyte has an argyrodite-type crystal structure. 4 . The composite solid electrolyte according to claim 1 , wherein the polymer of the polymer coating layer has a weight average molecular weight (Mw) of 1,000 g / mol to 1,000,000 g / mol. 5 . The composite solid electrolyte according to claim 1 , wherein the content of the polymer coating layer is 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the sulfide-based solid electrolyte particles. 6 . The composite solid electrolyte according to claim 1 , wherein the initial ion conductivity of the composite solid electrolyte is in the range of 0.01 mS / cm to 20 mS / cm.

7. The composite solid electrolyte according to claim 1, wherein When the composite solid electrolyte is exposed to an air atmosphere having a temperature of 25° C. and a relative humidity of 0.5% to 0.6%, the amount of hydrogen sulfide (H 2 S) generated in the first hour is 10 cm 2 per 1 g of the composite solid electrolyte. 3 the following.

8. A method for preparing the composite solid electrolyte according to claim 1, the method comprising the following steps: (A) mixing a polymer containing a repeating unit represented by Chemical Formula I with a sulfide-based solid electrolyte to prepare a mixture; and (B) heat-treating the mixture at a temperature higher than the melting point of the polymer to form a polymer coating on particles of the sulfide-based solid electrolyte: [Chemical Formula I] Wherein, in Chemical Formula I, X is fluorine (F) or chlorine (Cl).

9. The method according to claim 8, wherein the polymer comprises a repeating unit represented by Chemical Formula 1: [Chemical formula 1] 。 10 . The method according to claim 8 , wherein in the step (A), the polymer is mixed in an amount of 0.1 parts by weight to 10 parts by weight relative to 100 parts by weight of the sulfide-based solid electrolyte.

11. The method of claim 8, wherein the mixing is dry mixing.

12. The method according to claim 8, wherein the heat treatment temperature is in the range of 180°C to 250°C. 13 . An all-solid-state battery comprising the composite solid electrolyte according to claim 1 .

Citation Information

Patent Citations

  • Method of and system for manufacturing semiconductor device

    KR1020220109284A

Cited By

  • Solid electrolyte material and preparation method and application thereof

    CN120878956A

  • Solid-state electrolyte material, preparation method therefor, and use thereof

    CN120878956B